Development of a Game-Based e-Learning System with Augmented Reality for Improving Students’ Learning Performance - Shu-Hung Yang; Yu-Ying Wang; Ah-Fur Lai; Yi-Nan Lin; Gwo-Jen Chiou; Ming-Kuen Chen; Victor R. L. Shen; Chi-Yen Hsiung (International Journal of Engineering Education, 2020)
Currently, the school children usually spend a lot of time on the games in their recreational activities and some of them are even addicted to the games. Compared with other extracurricular activities, the e-Learning system reflects the fact that school children are very interested in the games. As a result, educators have lately craved to develop effective teaching activities that allow the school children to learn some subjects and to play the games simultaneously.  Therefore, this study is based on an e-Learning system which combines the serious game by Unity3D Game Engine with augmented reality (AR). Students are able to acquire their knowledge and to foster logical skills via this game-based e-Learning system.  According to its efficacy and utilities, this study has assessed and compared the game-based e-Learning system with the traditional learning and other e-Learning systems. The experimental results have indicated that the proposed game-based e-Learning system can outperform other existing systems.